2022
DOI: 10.1155/2022/7071877
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Adipose Mesenchymal Stem Cells Carrying miRNA-22-3p Promote Schwann Cells Proliferation and Migration through Downregulation of PTEN

Abstract: Peripheral nerve injury (PNI) is often resulting from trauma, which leads to severe and permanently disability. Schwann cells are critical for facilitating the regeneration process after PNI. Adipose-derived mesenchymal stem cells (ADSCs) exosomes have been used as a novel treatment for peripheral nerve injury. However, the underlying mechanism remains unclear. In this study, we isolated ADSCs and extracted exosomes, which were verified by transmission electron microscopy (TEM), nanoparticle tracking analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recently, it has been documented that adipose mesenchymal stem cell-derived exosomes carrying miRNA-22–3p promote Schwann cell proliferation and migration as well as dorsal root ganglion axon growth through downregulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN). 61 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been documented that adipose mesenchymal stem cell-derived exosomes carrying miRNA-22–3p promote Schwann cell proliferation and migration as well as dorsal root ganglion axon growth through downregulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN). 61 …”
Section: Methodsmentioning
confidence: 99%
“…However, miRNAs are known to play a role in Schwann cells’ proliferation and myelin regeneration. By knocking out ADSC-derived exosomes overexpressing miR-22-3p, we found that its effects on chromosome 10 (PTEN) activated the PI3K/Akt signaling pathway and contributed to the repair of the recurrent laryngeal nerve as well as the proliferation of Schwann cells [ 121 , 122 ].…”
Section: Stem Cell-based Evs and Nerve Regenerationmentioning
confidence: 99%
“…However, the mechanisms controlling the beneficial effects of M1 macrophage exosomes in the context of osteoblast differentiation are still unknown. It has been demonstrated that exosomes can translocate enriched miRNAs to target cells and perform their functions by binding to the 3′ untranslated regions (UTR) of intracellular mRNAs leading to translational repression or target degradation [ 27 ]. Herein, we present evidence that M1 macrophage-derived exosome miR-21a-5p is targeted to GATA2 to promote bone healing.…”
Section: Introductionmentioning
confidence: 99%